Complications following hip fracture: Results from the World Hip Trauma Evaluation cohort study. Issue 6 (June 2020) - Goh, En Lin; Lerner, Robin G.; Achten, Juul; Parsons, Nick; Griffin, Xavier L.; Costa, Professor Matthew L
Highlights: The WHiTE study combines patient- and hospital-reported outcomes for 8673 participants up to four months post-surgery for hip fracture. Following hip fracture, the most common general and surgery-related complications were chest and wound infections, respectively. The rates of complications reported provide a reference range against which future studies might be assessed. Abstract: Introduction: Hip fractures are common in people over 60 years of age, and are associated with significant disability, morbidity and mortality. The aim of this study was to record the incidence of complications in the first 120 days following hip fracture. Methods: The World Hip Trauma Evaluation (WHiTE) study is a multicentre, prospective cohort study conducted in National Health Service (NHS) hospitals in England and Wales. Participants are 60 years and older who received operative treatment for a hip fracture. We report the incidence of complications recorded by hospital staff until discharge from hospital and by participants at 120-days post-surgery. Results: An analysis of 8673 consecutive participants enrolled in the WHiTE study revealed the following risks of complications within the first 120 days: signs of wound infection (3.1%); dislocation (0.5%); failure of fixation (0.6%); peri‑prosthetic fracture (0.3%); overall revision surgery (0.9%); blood loss requiring transfusion (6.1%); chest infection (6.3%); urinary tract infection (5.0%); deep vein thrombosis/pulmonary embolus (1.8%); cerebrovascular accident (0.6%); acute coronary syndrome/myocardial infarction (0.6%); acute kidney injury (1.3%). Conclusion: The rates of complications reported here provide a reference range against which future studies might be assessed. Registration: ISRCTN63982700